# Solve the system of equations: 3x - 2y + 26 = 0, 5x + y + 26 = 0 using elimination method

*print*Print*list*Cite

Expert Answers

justaguide | Certified Educator

The system of equations

3x - 2y + 26 = 0 ...(1)

5x + y + 26 = 0 ...(2)

has to be solved for x and y.

(1) + 2*(2)

=> 3x - 2y + 26 + 10x + 2y + 52 = 0

=> 13x + 78 = 0

=> x = -78/13

=> x = -6

3*(2) - 5*(1)

=> 15x + 3y + 78 - 15x + 10y - 130 = 0

=> 13y - 52 = 0

=> y = 52/13

=> y = 4

**The solution of the given system of equations is x = -6 and y = 4**